Curial e Güelfa, un nou món per a un nou cavaller: espais literaris en un entorn humanístic. - BRIONGOS, JERONI MIGUEL (Scripta)
Curial e Güelfa shocks by its own modernity. In spite of some medieval reminiscences as a result of the atmosphere of chivalry it depicts, it belongs within the humanistic influence of the Italian Quattrocento. The author's mindful prose and his selection of literary sources or the variety of themes, correspond to the social and intellectual context of the day in Italy. Curial, as the main character in the novel, is a true example in his endeavour to blend arms and letters. The young knight must undergo a process towards adulthood which will also entail a personal crisis in the quest to achieve his goal: wedding Güelfa. With this aim in mind, and along with his chivalry frays, he will bow down on study, in the understanding that virtus itself will only be achieved through exertion in order to achieve the necessary nobilitas, which will on its own turn him into an integral being after acknowledging his own homo interior.